2006
DOI: 10.1111/j.1365-3083.2006.001764.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of MAP Kinase‐Dependent Apoptotic Pathway in Innate Immune Responses and Viral Infection

Abstract: Mitogen-activated protein (MAP) kinase cascades are multifunctional signalling networks that influence cell growth, differentiation, apoptosis and cellular responses to stress. Apoptosis signal-regulating kinase 1 (ASK1) is a MAP kinase kinase kinase that triggers apoptogenic kinase cascade leading to the phosphorylation/activation of c-Jun N-terminal kinases (JNK) and p38-MAP kinase, which are responsible to induce apoptotic cell death. This pathway plays a pivotal role in the transduction of signals from dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 65 publications
2
52
0
1
Order By: Relevance
“…Ceramide has been shown to induce apoptosis through the activation of MAPK, 13,40 and inhibitors of the p38 and ERK1/2 MAPK pathways reduce it. 13 In line with that work, we found that treatment of cells with a p38-specific inhibitor substantially reversed the PPMP-induced reduction in antigen presentation by CD1d; however, the addition of an ERK1/2 pathway inhibitor did not.…”
Section: Discussionmentioning
confidence: 99%
“…Ceramide has been shown to induce apoptosis through the activation of MAPK, 13,40 and inhibitors of the p38 and ERK1/2 MAPK pathways reduce it. 13 In line with that work, we found that treatment of cells with a p38-specific inhibitor substantially reversed the PPMP-induced reduction in antigen presentation by CD1d; however, the addition of an ERK1/2 pathway inhibitor did not.…”
Section: Discussionmentioning
confidence: 99%
“…In response to inflammatory signals including microbial or viral infection, UV-irradiation, and burning, the MAP kinase cascade is activated through phosphorylation of p38, Erk1/2, and JNK, together with activation of NF B (Sumbayev and Yasinska, 2006). This MAP kinase activation is terminated, and returns to base levels within several hours, following its stimulation (Pouyssegur et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis can act as an innate defense that restricts viral spread by eliminating infected cells and triggering pathogen recognition pathways (58). Alternatively, cell death could directly contribute to the spread and replication of WNV.…”
Section: Vol 81 2007 Apoptosis Contributes To West Nile Virus Pathomentioning
confidence: 99%